2013
DOI: 10.1371/journal.pone.0067379
|View full text |Cite
|
Sign up to set email alerts
|

Altered Methylation of IGF2 Locus 20 Years after Preterm Birth at Very Low Birth Weight

Abstract: IntroductionPeople born preterm at very low birth weight (VLBW, ≤1500g) have higher rates of risk factors for adult-onset diseases, including cardiovascular diseases and type 2 diabetes. These risks may be mediated through epigenetic modification of genes that are critical to normal growth and development.MethodsWe measured the methylation level of an imprinted insulin-like-growth-factor 2 (IGF2) locus (IGF2/H19) in young adults born preterm at VLBW and in their peers born at term. We studied 158 VLBW and 161 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…We found no persisting differences at 1 year of age. Whether further differences will emerge over longer follow-up is unknown; alterations in DNA methylation at key DMRs controlling the expression of IGF2 have been reported in adults exposed to altered nutrition or prematurity (16, 17, 42); however, these were not longitudinal studies, so that any differences may have arisen postnatally. Additionally, these studies may have been complicated by the phenomenon of reverse causation, where the development of disease leads to changes in DNA methylation rather than vice versa (41).…”
Section: Discussionmentioning
confidence: 99%
“…We found no persisting differences at 1 year of age. Whether further differences will emerge over longer follow-up is unknown; alterations in DNA methylation at key DMRs controlling the expression of IGF2 have been reported in adults exposed to altered nutrition or prematurity (16, 17, 42); however, these were not longitudinal studies, so that any differences may have arisen postnatally. Additionally, these studies may have been complicated by the phenomenon of reverse causation, where the development of disease leads to changes in DNA methylation rather than vice versa (41).…”
Section: Discussionmentioning
confidence: 99%
“…Low birth weight has been linked with DNA methylation 20 years later 28. Social and physical exposures such as nutrition, psychosocial stressors and toxicants,29 all of which can be socially patterned, change DNA methylation.…”
mentioning
confidence: 99%
“…Premature birth due to obstetric infections, such as chorioamnionitis and funisitis, was found to be linked with significant DNA methylation at PLAGL1 imprinted-related gene (Liu et al, 2012). In a retrospective study, Wehkalampi et al (2013) reported that young adults born preterm exhibited genomewide DNA methylation alterations that might be suggestive of long-lasting epigenetic modifications related to preterm birth. Although these studies document an association between premature birth and altered epigenetic markers, it should be noted that methylation was not assessed at the level of specific candidate genes with functional implications for the HPA axis (i.e., NR3C1 gene methylation).…”
Section: Early Adverse Events and Dna Methylation: Research With Humansmentioning
confidence: 99%